2022
DOI: 10.1002/jcv2.12078
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effects between maternal mental health and adolescent internalizing problems across six years in Northern Ireland

Abstract: Background: Emerging evidence indicates the existence of bidirectional relations between mothers' mental health and adolescent adjustment, but few studies have examined these relations in contexts of high environmental adversity, including economic deprivation and political violence. Given other empirical connections between political violence and adolescent adjustment problems, the impact of child adjustment problems on maternal mental health may be exacerbated in contexts of sectarian violence.Methods: Addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…This may reflect the demands of both caretaking and supporting home schooling. Also of note, this mirrored the pattern of mental health symptoms seen in the children of the same sample (Creswell et al, 2021) in line with previous evidence suggesting a bidirectional relationship between parental and child mental health (Luningham et al, 2022). Unlike Pierce et al (2020) who found particularly elevated psychological distress symptoms among parents of preschool children in the first UK national lockdown, we found that having pre-school-aged children (< 4 years) only was associated with decreasing anxiety scores.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This may reflect the demands of both caretaking and supporting home schooling. Also of note, this mirrored the pattern of mental health symptoms seen in the children of the same sample (Creswell et al, 2021) in line with previous evidence suggesting a bidirectional relationship between parental and child mental health (Luningham et al, 2022). Unlike Pierce et al (2020) who found particularly elevated psychological distress symptoms among parents of preschool children in the first UK national lockdown, we found that having pre-school-aged children (< 4 years) only was associated with decreasing anxiety scores.…”
Section: Discussionsupporting
confidence: 90%
“…This may reflect the demands of both caretaking and supporting home schooling. Also of note, this mirrored the pattern of mental health symptoms seen in the children of the same sample (Creswell et al, 2021) in line with previous evidence suggesting a bidirectional relationship between parental and child mental health (Luningham et al, 2022). Unlike including disruptions to sleep, mood and quality of relationships (Illingworth et al, 2022) as well as ongoing concerns about disruption, delays and uncertainty in education and recreational activities at a key point in the young person's life that may have a significant bearing on their future (Pearcey et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This may reflect the demands of both caretaking and supporting home schooling. Also of note, this mirrored the pattern of mental health symptoms seen in the children of the same sample (Creswell et al, 2021) in line with previous evidence suggesting a bidirectional relationship between parental and child mental health (Luningham et al, 2022). Unlike Pierce et al (2020) who found particularly elevated psychological distress symptoms among parents of preschool children in the first UK national lockdown, we found that having pre-school-aged children (< 4 years) only was associated with decreasing anxiety scores.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, Pierce et al (2020) showed psychological distress in the first UK national lockdown particularly increased for those living with any younger (0-5-years-old) rather than just older (6-15-years-old) children. The impact of the pandemic on children's mental health may also have affected parental mental health (Luningham et al, 2022), and this may have also varied with child age. For example, parents in the UK Co-SPACE study reported greater increases in mental health symptoms among primary school aged children, compared to secondary aged children, in the first UK national lockdown (Waite et al, 2021).…”
Section: Introductionmentioning
confidence: 99%